Теорія взаємодії в інноваційних процесах - Лісовська, Л. С.; Lisovska, L. (Видавництво Львівської політехніки, 2020)
Досліджено та обґрунтовано авторську теорію взаємодії у інноваційних процесах. Доведено необхідність перегляду положень сучасних теорій у сучасних умовах, оскільки вони ускладнюють можливості та призводять до неефективності використання для здійснення інноваційних процесів на різних рівнях. Розвиток інноваційного процесу визначається показниками налагодження взаємодії між етапами та учасниками інновацій. Досліджено основні теорії економічного та особистісного розвитку, наявні в інформаційному полі менеджменту та інноватики. Автор дослідила теоретичні положення теорій особистісного розвитку, теорій інноваційного розвитку, теорій взаємодій та теорій партнерства, теорій інноваційної співпраці. Проаналізовано основні теоретичні внески цих теорій, а також можливість їх використання для формування авторської теорії взаємодії у інноваційних процесах. На підставі аналізування і виконаних досліджень автор виокремила положення теорії взаємодії у інноваційних процесах, які враховують зміну парадигми інноваційного процесу, еволюцію моделей інноваційних процесів, види взаємодій у інноваційних процесах. Авторська теорія містить визначення постулатів, гіпотез та очікуваних результатів. Розроблену теорію можна використовувати як підґрунтя для забезпечення інноваційного розвитку регіонів та країни за умови формування та реалізації дієвого механізму налагодження взаємодії між учасниками інноваційного процесу.

The article substantiates the provisions and components of the author’s theory of interaction in innovation processes. The author proved the importance of such a theory by the existence of the dependence of the development of innovation processes on ensuring interaction in various forms, the need to develop it – changing the paradigm of the innovation process, the evolution of models of innovation processes, the development of “open innovation”. The developed theory of interaction in innovation processes is based on the basic theories of development of the person, the organization, theories of interactions and theories of innovative development. To form the theory of interaction in innovation processes, the author grouped economic theories by content and the order of increasing influence on the parameters of innovation development. Grouping of theories allows to single out the priorities of theory construction in the chain “personorganization-interaction-innovation-innovation cooperation”, to determine the place and significance of elements of interaction system in construction and development of innovation processes, to substantiate indicators of evaluation of efficiency of formation and development of interaction in innovation processes. The author’s theory is distinguished by the author’s attempt to present in the relationship and complementary priority areas of innovation development at different levels, separated from the developed economic theories and theories of innovation and personal development by eliminating their weaknesses and debates. The author singled out five groups of theories: Theories of personal development (Theories of thinking, Theories of creativity, Theories of leadership, The concept of knowledge management), Theories of interactions, Theories of social interaction, Model of dyadic interaction (interaction in dyad), Concept of symbolic interactionism), Partnership Theories (Quality Theory, Competitiveness Theory, Utility Theory, Value Chain Concept, Value Theories, Relationship Marketing), Theories of Innovative Development (Cycle Theory (“Long Waves”), Classical Theory of Innovation, Neoclassical Theory of Psychological Innovation, innovation, “Economic Theory of Industrial Innovation”, Theory of Innovation Economics), Theories of Innovation Cooperation (Theories of the Innovation Ecosystem, Concepts of the four-component spiral Quadruple Helix (QH), Network Theories, Theories of Open Innovation). The author’s theory contains definitions of postulates, hypotheses and expected results. The main hypothesis of the proposed theory is to ensure the development of interaction systems in innovation processes to increase productivity. The developed theory can be used as a basis for ensuring the innovative development of regions and countries, provided the formation and implementation of an effective mechanism for establishing interaction between participants in the innovation process. As a basis for the formation of the mechanism, the author proposes to choose the criteria of the value of interaction, as well as the principles of interaction marketing.
Interaction theory in innovation processes
Keywords: інноваційний розвиток; постулати; гіпотеза; взаємодія; взаємодія у інноваціях; інноваційний процес; відкриті інновації; theory; innovative development; postulates; hypothesis; interaction; interaction in innovations; innovation process; open innovations; O31;; O12;; D70;; D25; 658.001.76; 330.341.1